2020
DOI: 10.1101/2020.05.01.20087759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Temperature on the Transmission of COVID-19: A Machine Learning Case Study in Spain

Abstract: The novel coronavirus has already spread to almost every country in the world and has infected over 3 million people. To understand the transmission mechanism of this highly contagious virus, it is necessary to study the potential factors, including meteorological conditions. Here, we present a machine learning approach to study the effect of temperature, humidity and wind speed on the number of infected people in the three most populous autonomous communities in Spain. We find that there is a moderate invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
4
14
0
Order By: Relevance
“…Equation (9a), however stresses that temperature and humidity are of secondary relevance to the virus spread rate, since they are inter-regime influences, rather than intra-regime ones. The very existence of this relevance (together with its being of limited or secondary nature only) seems to be in line with the reported disparity among the cited references [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Qualitative reasoning [30, [35][36][37] show that, according to (9a), temperature and humidity have opposing influences on virus spread rate.…”
Section: Derivation Of the Virus Spread Rate Via The Dimensional Basissupporting
confidence: 67%
See 1 more Smart Citation
“…Equation (9a), however stresses that temperature and humidity are of secondary relevance to the virus spread rate, since they are inter-regime influences, rather than intra-regime ones. The very existence of this relevance (together with its being of limited or secondary nature only) seems to be in line with the reported disparity among the cited references [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Qualitative reasoning [30, [35][36][37] show that, according to (9a), temperature and humidity have opposing influences on virus spread rate.…”
Section: Derivation Of the Virus Spread Rate Via The Dimensional Basissupporting
confidence: 67%
“…A notable exception to the general trend in the papers surveyed is the work of Jamil et al [50], who tested the hypothesis that COVID-19 spread is temperature-dependent using data derived from nations across the world and provinces in China, and found no evidence of a pattern between spread rates and ambient temperature, suggesting that the SARS-CoV-2 is unlikely to behave as a seasonal respiratory virus. Abdollahi and Rahbaralam [51] found that there is a moderate inverse correlation between temperature and the daily number of infections. Briz-Red贸n and Serrano-Aroca [52] suggest that 'the disparate findings reported seem to indicate that the estimated impact of hot weather on the transmission risk is not large enough to control the pandemic.'…”
Section: Derivation Of the Virus Spread Rate Via The Dimensional Basismentioning
confidence: 99%
“…Most studies (33 out of 61) suggest a negative correlation between COVID-19 and temperature. A negative correlation was found in worldwide studies (Arumugam et al, 2020;Caspi et al, 2020;Chiyomaru and Takemoto, 2020;Notari, 2020;Pirouz et al, 2020;Sajadi et al, 2020;X Wu et al, 2020;Yu, 2020), in California (Gupta and Gupta, 2020), Japan (Ujiie et al, 2020), Ghana (Abdul et al, 2020), Spain (Abdollahi and Rahbaralam, 2020;Tob铆as and Molina, 2020), Italy (Livadiotis, 2020) and in China (Oliveiros et al, 2020;Qi et al, 2020;Shi et al, 2020;Sil and Kumar, 2020). However, other studies came to the opposite conclusion (6 out of 61): a positive correlation between COVID-19 and temperature in Jakarta (Tosepu et al, 2020) and New York (Bashir et al, 2020), or no association (9 out of 61) in countries such as Spain (Briz-Red贸n and Serrano-Aroca, 2020), Iran (Ahmadi et al, 2020;Jahangiri et al, 2020), Nigeria (Taiwo and Fashola, 2020) and in a worldwide study (Jamil et al, 2020).…”
Section: Findings 31 Meteorological Variablesmentioning
confidence: 89%
“…Contrastingly, Bashir et al (2020) and Oliveiros et al (2020) have not observed any correlation of COVID-19 pandemic spread with wind speed in China. Abdollahi and Rahbaralam (2020) have also witnessed a weak correlation of wind speed with COVID-19 in Spain. Again, rainfall has not been found associated with COVID-19 pandemic spread in NCT of Delhi (Table 1), which has been found consistent with the results reported by Tosepu et al (2020).…”
Section: Correlation Between Climatic Variables and Covid-19 Pandemicmentioning
confidence: 99%